Identifkasi Komoditas Pertanian untuk Peningkatan Pendapatan Masyarakat Pada Lahan Gambut di Desa Cot Mee Kecamatan Tadu Raya Kabupaten Nagan Raya. - Bagio Bagio; Yusya Abubakar; Ashabul Anhar; Akhmad Baihaqi (Universitas Teuku Umar, 2021)
The clearing and use of peatlands is carried out extensively and pays moreattention to economic value but marginalizes its ecological function which causes damage to peatlands. Community empowerment is expected to make people wiser in managing peat. The location of the service is in Cot Mee Village, Tadu Raya District, Nagan Raya Regency. The method used is discussion, going to the field, and making demonstration plots. Field results show that most of the peatlands in Cot Mee Village have experienced drought, due to a lack of knowledge in managing the peat ecosystem. There are two (2) is valuable commodity cultivated corn and pineapple, with revenue cost ratio (R / C ratio) for commodity corn amounted to 1.904 and 2.162 of pineapple.